Furosemide Administration Affects Mineral Excretion in Exercised Thoroughbreds. (June 2014) - Pagan, J; Waldridge, B; Whitehouse, C; Fuchs, S; Goff, M
Abstract : Introduction: Furosemide is widely administered to Thoroughbred and Standardbred racehorses to reduce the incidence and severity of EIPH. The magnitude and duration of mineral loss following furosemide administration has not previously been measured in horses. Methods: Six fit Thoroughbreds (age 6.8 ± 1.2 y; bwt 585 ± 19 kg) were used in a 3 x 3 Latin square design trial to measure the effect of furosemide on urinary and fecal mineral excretion for 24 h before (−24 h) and 24 h, 48 h and 72 h after a standardized exercise test (SET) on an inclined (3 o ) high speed treadmill. The treatment groups consisted of an untreated control (C) and two groups (F and FE) which received furosemide (0.5 mg/kg, IV) 4 h before the SET. C and F were fed 60 g/d NaCl and (FE) was fed 200 g/d of an electrolyte mix (14 g K, 37.7 g Na and 43.3 g Cl) for 21 days before the SET. Following the SET the FE group was supplemented with an additional 10 g/d Ca and 10 g/d Mg. Results: Urinary Ca, P, Na and Cl excretion increased 24 h post treatment in the F and FE groups (P<0.05). 72 h Ca and Cl balance was decreased in F (P<0.05) and 72 h Mg and Cl balance was decreased in FE (P<0.05). The digestibility of P and Mg was decreased in FE (P<0.05) and Na digestibility was increased in F and FE (P<0.05). Conclusions: A single dose of furosemide negatively affected calcium balance in horses for 72 h post administration. Further research is needed to assess the effect of chronic furosemide use in racehorses on mineral balance and soundness. Ethical Animal Research: Study approved by the Kentucky Equine Research Institutional Animal Care and Use Committee.Sources of funding: Kentucky Equine Research.Competing interests: none.